Emerging pedagogical contexts and disruptive practices in secondary education. - Cortés-González, Pablo; Prados-Megías, Esther; Campos-Leal, Juan Manuel; Hinojosa San Eufrasio, José Antonio; Leite-Méndez, Analía Elizabeth; Rivas-Flores, José Ignacio (My University, 2019)
In this contribution we present both the framework and the first advances of one of the four cases studied that make up the research project 'Nomads of knowledge in emerging pedagogical contexts: mapping disruptive practices in Secondary Education ", funded by the" COTECT Foundation for innovation”. The project is based on the needs and demands arising in the current context of the "knowmadic society" (Cobo, 2013), in which formal education is developed within the framework of the augmented society and multiple literacies. We intend to examine the life inside and outside the schools and their classrooms, where interactions are proliferated around technological creations, communication platforms, videogames or mobile apps. All these are environments where learning experiences can be used by secondary schools and by the professionals who work in them (Gorodetsky & Barak, 2014). In this paper, in addition to presenting some general issues of the project, we focus on one of the case studies, related to ‘José Manuel Torrijos Secondary School’ (onwards Torrijos) located in a socio-culturally disadvantaged neighbourhood of the city of Malaga. The profile of students mainly comes from broken families, from very diverse ethnic groups and with large socio-educational deficits. Also, until recently, the role of teachers has been unstable and little interest in a deep educative school project.
Keywords: Abandono de los estudios; Orientación escolar; Preventing dropout and improving results for children and youth; Interprofessional collaboration; Youth and schools at risk; Network experience